Sosialisasi dan Edukasi Konservasi Penyu di KKP3K Paloh “Menjaga Penyu, Menjaga Alam, Menjaga Kehidupan” - Yuliono, Agus; Safitri, Ikha; Sofiana, Mega Sari Juane; Susanto, Hendro; Zulfian, Zulfian (Journal of Community Development, 2024)
Paloh District is a turtle conservation area designated by the Minister of Maritime Affairs and Fisheries. This conservation area is managed by local community groups and the WWF-Indonesia Foundation under the authority of the West Kalimantan Province Maritime and Fisheries Service. Turtles are protected biota because of their endangered status. However, the community, especially local residents, do not yet have awareness of the importance of protecting this biota and also maintaining the balance of the surrounding ecosystem. Several cases occurred in Paloh, namely poaching for turtle eggs, degradation of turtle nesting beach habitat and marine debris pollution. Therefore, socialization and education on turtle conservation needs to be carried out, especially in the Paloh turtle conservation area. Activity participants are pupils, students and the community. The education and socalization provided includes the types of turtles, their conservation status and the protection efforts that can be taken. The aim of this community services was provided awareness for the community so that they participate in efforts to protect turtles and their habitat. Participants were very enthusiastic in taking part in the entire series of activities. There were five (5) participants who answered the questions correctly and received gifts from the organizing committee.